An Analysis of the Macroeconomic Variables Impacting the Indian Stock Market at NSE Nifty 50 - Prakash, R. P. (Indian Journal of Research in Capital Markets, 2021)
The main purpose of the study was to understand a long-term relationship of the external macroeconomic factors and the Nifty 50 index of the National Stock Exchange (NSE). Five major macroeconomic factors namely, foreign exchange reserves, prices of crude oil, foreign institutional investment, balance of payments, and gold prices were considered to know the cause of these external macroeconomic factors on NSE Nifty 50. Monthly data of the above variables were being considered for the study from January 2016 to December 2020, that is, for a period of 5 years. To understand the relationship among the variables, an attempt was made to use the Augmented Dickey – Fuller (ADF) test to ascertain whether the data used were stationary or not, and to know the extent of influence of independent variables on dependent variables by running the multiple regression. It was observed that out of all the factors considered for the study, bearing crude oil, no factor had a relationship with the market index (NSE Nifty 50). It was also found that the stock market became a weak form as no significant relationship existed during the study period.